ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN UANG DI INDONESIA - Hidayat, Fahrul; Itsnaini, Fatmi; Lathifah, Siti Nurul; Jannah, Virda Azzahrotul (IQTISODINA, 2024)
A request for money is an amount of money requested or desired by the community. The demand for money has an important role for monetary policy authorities in determining the right policies to maintain economic stability. Money demand analysis is an analysis of the economic magnitude needed to support a policy taken by the government in the monetary field. The purpose of the study is to analyze the effect of Inflation, Interest Rates and E-Money on Money Demand in Indonesia. This study uses a qualitative approach. This study used quantitative research methods. The data used is the demand for money for the period 2021-2023. Data sources from the Central Bureau of Statistics and Bank Indonesia. This study aims to determine the factors that affect the demand for money in Indonesia in the 2021-2023 period.